PENGARUH SELF-EFFICACY DAN CRITICAL THINKING TERHADAP ACADEMIC PERFORMANCE YANG DIMEDIASI ACADEMIC ENVIRONMENT: STUDI PADA MAHASISWA UNIVERSITAS BUDI LUHUR - Anwar, Syaiful (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
This research is motivated by the importance of improving students' academic performance, which is influenced by both internal and external factors, particularly self-efficacy, critical thinking, and the environment. Numerous academic challenges faced by students—including low motivation, lack of self-confidence, insufficient critical thinking skills, and an unconducive learning environment—have become central issues in higher education. This study aims to examine the effect of self-efficacy and critical thinking on the academic performance of students at Budi Luhur University and to assess whether the environment can moderate these relationships. The approach used is quantitative, employing a survey method and data analysis using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). Data were collected from 130 active students who had completed at least 90 credit units, with variables measured using a Likert scale. The results indicate that critical thinking and the environment have a significant effect on academic performance, while self-efficacy does not show a significant direct effect. Additionally, the environment does not moderate the influence of either self-efficacy or critical thinking on academic performance. These findings imply the need to enhance the quality of the academic environment and foster students’ critical thinking skills. Meanwhile, efforts to improve self-efficacy should be accompanied by a more supportive environment to achieve a greater impact on academic performance.